MANAGEMENT OF SARCOPTIC AND PSOROPTIC MANGE INFESTATION IN RABBITS (ORYCTOLAGUS CUNICULUS) WITH INJECTABLE IVERMECTIN - E. Tamileniyan; M. Jeevitha; K. Karthika; A. Latchumikanthan; M. Veeraselvam; V. R. Kundave; M. Saravanan; R. Velusamy (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study presents two clinical cases in Chinchilla and Himalayan rabbits, exhibiting symptoms such as alopecia, skin lesions, and ear lesions. Skin scrapings and fecal samples were collected and processed, revealing the presence of Sarcoptes scabiei mites, Psoroptes cuniculi mites, and Eimeria oocysts. Treatment involved subcutaneous administration of Ivermectin (0.2 mg/kg), accompanied by supportive and topical application of Benzyl benzoate. The rabbits displayed clinical improvement, with complete recovery observed within 30 days.